Derivative Including Quadratures Based on Kernel Decomposition - (:unkn) unknown (AMER INST PHYSICS, 2011)
Gauss quadrature is a commonly used method for approximating univariate (even multivariate in certain cases) integrals. In Gauss quadrature the values of the function to be integrand, at certain points of the integration, are used. In this work we attempt to bring extra flexibility to Gauss Quadrature by also using the derivative of the function to be integrated.
Keywords: Quadrature; Gauss Quadrature